A Mobile Wireless Sensor Coverage Optimization Method for Bridge Monitoring - Cong Mu; Jiguang Yang; Jiuyuan Huo (Sensors)
Aiming at the problem of resource allocation optimization of heterogeneous mobile wireless sensor (HMWS) networks in bridge structural health monitoring, this study proposes an enhanced coverage strategy for heterogeneous sensors based on an improved Hiking Optimization Algorithm (HOA). This paper integrates the Good Point Set theory with a heterogeneous degree-of-freedom t-distribution perturbation mechanism to improve the basic HOA, developing the GPTHOA with global optimization characteristics. Based on this, a virtual force-guided HMWS coverage enhancement strategy (the VF-GPTHOA) is proposed. After determining the optimal deployment scheme, the GPTHOA is further employed to optimize node movement trajectories, minimizing the movement distance. Simulation results show that when deploying 60 heterogeneous sensors of three types in a 40 m × 200 m bridge model (BM), the coverage rate (CR) of the VF-GPTHOA reaches 97.07%, which represents improvements of 13.81%, 4.18%, 15.81%, 2.52%, and 12.44% over DE, MA, GWO, SSA, and HOA, respectively. In dynamic node scale scenarios, the VF-GPTHOA maintains optimal coverage performance, demonstrating its robustness and applicability in engineering practice.